Price and taste analysis of coffee consumer satisfaction Janji Jiwa Batam City - Hendri Herman; Christoper HP Sitanggang; Sufiyandi; Aldino Masni Lova (Enrichment : Journal of Management, 2023)
The purpose of this study is to determine the effect of price and taste on consumer satisfaction of Kopi Janji Jiwa. The population in this study is consumers of Kopi Janji Jiwa. The sample in this study was 100 consumers. Data was obtained by distributing questionnaires to respondents. The data that has been collected will be processed using the SPSS application. Sampling method using simple random sampling. From the results of the study, it is known that price has a significant effect on consumer satisfaction. Taste has a significant effect on consumer satisfaction. And simultaneously price and taste have a significant effect on consumer satisfaction. The r square value in this study was 0.325 or 32.5%. This means that price and taste are able to explain consumer satisfaction by 32.5%. While the remaining 67.5% was influenced by other variables that were not included in this research model